Social connections related to health and well-being needs identified by children and adolescents affected by displacement in Lebanon: a participatory research study - Tanvi Jain; Lynsey Cooper; Nicole Khauli; Kathleen Pike; Brigitte Khoury; Sabrina Hermosilla (Elsevier, 2025)
Introduction: The social connections surrounding children and adolescents support them in facing challenges and seeking help, ultimately acting as a protective factor in their mental, physical, and behavioral health outcomes across the life course. In complex contexts of political instability and dislocation, these social resources are often fractured, strained, or altogether unavailable, which restricts access to essential services and affects outcomes for these populations. This study aims to identify, characterize, and visually depict social connections related to the health and well-being needs of children and adolescents affected by displacement in Lebanon, by pilot testing the Participatory Assessment Tool for Mapping Social Connections (PATMSC). We hypothesize that this unique methodology will identify and describe different social connections by group quickly and efficiently. Methods: An initial scoping review of scientific and grey literature followed by stakeholder interviews identified nutrition, mental health, and abuse scenarios that guided the PATMSC (a mixed- method data collection tool that identifies and visualizes types and qualities of social connections) topics. The PATMSC was piloted among children, caregivers, and providers affected by displacement in Lebanon. Results: There were seven groups (Syrian children, Syrian adolescents, Syrian caregivers, Lebanese/Palestinian children, Lebanese/Palestinian adolescents, Lebanese/Palestinian caregivers, and providers) with a total of 42 participants across the PATMSC workshops. Syrian children identified the most connections across all scenarios (66 nodes) and Lebanese/Palestinian adolescents identified the fewest connections across all scenarios (26 nodes). Family and community nodes were highly connected across all scenarios. 56% of participants asked their family connections for help. Family connections were the most used by children (71%) and provider (33%) subgroups. Participants were asked for help by family connections the most (59%). Within subgroups, children (84%), Lebanese/Palestinian participants (73%), providers (50%), and caregivers (36%) were also asked for help by family connections the most. Discussion: The study highlights that children, adolescents, and their caregivers in displaced settings in Lebanon have varied social connections when exploring resources related to key areas of concern. Overall, there is an importance placed on the role of family members in their social networks. However, the social connections and resources available differ depending on the circumstances, as evidenced by the variation in connections named across the three scenarios. Understanding the components of social networks, what drives them, and how they differ by sector, is essential in planning and maintaining programs and policies that meet evolving needs in resource-constrained settings.